Efektivitas Pengelolaan Zakat, Infaq dan Sedekah (ZIS) di Baitul Mal Provinsi Aceh - Bukhari Usman; Yuliana Yuliana; Yuni Ayu Safitri; Farah Uliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Abstract: This study aims to determine the effectiveness of the management of zakat, infaq and alms in Baitul Mal Province. The object of this research is the report on the receipt of Zakat, Infaq and Alms (ZIS) of Aceh Province in 2013-2019. This study uses a descriptive method with a quantitative approach, namely to formulate attention to the problems at hand, where the data collected is compiled and analyzed so that it can provide information on existing problems. The results showed that the number of Zakat, Infaq and Alms Zakat, Infaq and Alms (ZIS) receipts in Baitul Mal, Aceh Province from 2013 to 2019 has increased. In 2014 it increased by 20.06 percent, 2015 by 3.71 percent,2016 was 3.67 percent, 2017 was 34.54 percent, 2018 was 10.08 percent and 2019 was 2.95. The effectiveness of receiving Zakat, Infaq and Alms (ZIS) in Baitul Mal, Aceh Province is very effective, in 2013 it was 266 percent, 2015 amounted to193 percent, 2016 by 137 percent, 2017 by 232 percent, 2018 by 204 percent and 2019 by 188 percent, and quite effective in 2014, which amounted to88 percent. The effectiveness of the distribution of Zakat, Infaq and Alms (ZIS) in Baitul Mal, Aceh Province was very effective in 2013 by 518 percent and effective in 2014 by 100 percent, 2015 by 100 percent, 2016 by 100 percent, 2017 by 99.25 percent, 2018 by 100 percent and 2019 by 100 percent. It can be concluded that the effectiveness of the management of Zakat, Infaq and Alms (ZIS) in Baitul Mal Aceh was very effective in 2013 which was 266 percent in terms of revenue realization and 518 percent in terms of distribution realization.